Challenges in reading skill acquisition among students in the Language Preparatory Program at STIBA Ar Raayah, Sukabumi (A descriptive study) - Jajang Komaludin (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2025)
Students of the Language Preparation Program at STIBA Ar Raayah, Sukabumi, face challenges in improving their reading skills, including reading speed, phonological awareness, text comprehension, and fluency, all of which affect their academic progress. This study aims to describe and address the reading difficulties faced by these students at STIBA Ar Raayah, Sukabumi. It adopts a descriptive-analytical approach using a qualitative method, where data were collected through direct observation, interviews, and testing, then analyzed using the Miles and Huberman model, which includes four steps: data collection, classification, display, and conclusion. The study found that students face multiple challenges in acquiring reading skills, most notably weak oral reading, word repetition, neglect of punctuation, and difficulty in accurate pronunciation. They also struggle with distinguishing between short and long vowels, similar-sounding letters, phonological awareness, and reading fluency. To address these difficulties, the study suggests increasing reading activities with a focus on comprehension and speed, training students on vocabulary in various contexts, developing fluency through targeted activities, as well as training teachers and encouraging students to read beyond the curriculum.Keywords: Language Preparation Students, Reading Difficulties and Solutions, Reading Skills, STIBA Ar Raayah